2015
DOI: 10.1136/bjophthalmol-2014-306508
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of the AdenoPlus point-of-care system in detecting adenovirus in conjunctivitis patients at an ophthalmic emergency department: a diagnostic accuracy study

Abstract: The AdenoPlus test has a high specificity for diagnosing adenoviral conjunctivitis, but in this clinical setting, we could not reproduce the high sensitivity that has been previously published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…The results strongly suggested that SAI is useful for avoiding false negative findings compared with IC. Previous tests using IC obtained higher detection limits than PCR and virus isolation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results strongly suggested that SAI is useful for avoiding false negative findings compared with IC. Previous tests using IC obtained higher detection limits than PCR and virus isolation …”
Section: Discussionmentioning
confidence: 99%
“…Previous tests using IC obtained higher detection limits than PCR and virus isolation. 11,23 One possible explanation is that the colloidal gold and colored latex particles used for labeling in IC do not have high sensitivity for color development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second-generation point-of-care diagnostic immunoassay that can detect the virus hexon antigen is available [44]. The result of the AdenoPlus (Quidel, San Diego, CA) returns quickly; though specificity is high, sensitivity can range widely [45,46]. As such, AdenoPlus may be better used to diagnose patients with adenoviral conjunctivitis than to screen patients with possible adenoviral conjunctivitis.…”
Section: Types Of Adenoviral Ocular Infections Diagnosis and Antibimentioning
confidence: 99%
“…Specifically, depending on publication and location, when compared with PCR, AdenoPlus has a sensitivity of 39.5-90% and specificity of approximately 96% [45,46]. Reasons for the range of sensitivity values may be different swabbing techniques or different profiles of endemic adenoviral serotypes depending on geographical area.…”
Section: Types Of Adenoviral Ocular Infections Diagnosis and Antibimentioning
confidence: 99%